Efeito agudo da fotobiomodulação de corpo inteiro na rigidez arterial de indivíduos com hipertensão arterial: um ensaio clínico duplo cego, sham controlado e randomizado - Rossi, João Marcos Dariolli (Universidade Federal de São Carlos, 2025)
Hypertension is the main risk factor for cardiovascular diseases, with a great impact on public health. Hypertension is frequently related to arterial stiffness, a condition that predicts the risk for cardiovascular events and mortality. Photobiomodulation (PBM) therapy has a potential hypotensive mechanism, that can modulate arterial wall distension and then improve arterial stiffness indicators, showing promise as a therapeutic resource in the treatment of hypertension. However, until now, no studies have been found that have investigated these potential PBM effects, especially with emphasis on full-body PBM, that can achieve systemic effects. Objectives: To evaluate the acute effect of full-body PBM on arterial stiffness of individuals with hypertension. Material and Methods: This is a randomized double-blind and sham-controlled clinical trial. Participants (n=21) aged 40 to 60 years old, diagnosed with hypertension and using control drugs were equally, randomly and secretly allocated into one of 2 groups: Full-body PBM group; and Full-body PBM Sham group. Participants were assessed for arterial stiffness in the pre- and post-intervention moments by carotid-femoral pulse wave velocity analysis. Participants received a single application of PBM, which, depending on the group, was an active or sham full-body irradiation from a LED panel. Data homogeneity and normality were verified by the Levene and Shapiro-Wilk tests, which determined the choice of subsequent tests. A statistical significance of 5% was considered. Results: The pulse wave velocity (PWV) values between the pre- and post-therapy assessments showed no statistically significant differences in either group. However, the active group demonstrated a reduction from 8.18 ± 1.40 m/s to 7.89 ± 0.91 m/s, whereas the sham group showed an increase from 6.26 ± 0.64 m/s to 6.56 ± 0.94 m/s. Aortic systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) values exhibited significant reductions in the active group, decreasing from 132.4 ± 10.7 to 124.3 ± 9.33 mmHg, from 90.2 ± 10.02 to 85.75 ± 8.65 mmHg, and from 108.4 ± 10.51 to 101.4 ± 10.10 mmHg, respectively. In contrast, the sham group showed no statistically significant differences between pre- and post-therapy assessments, with aortic SBP, DBP, and MAP changing from 124.2 ± 11.41 to 123.3 ± 13.45 mmHg, from 84.55 ± 11.88 to 84.45 ± 13.54 mmHg, and from 101.4 ± 11.82 to 99.36 ± 14.33 mmHg, respectively. Conclusion: The findings suggest a possible association between photobiomodulation therapy and improvements in outcomes related to arterial stiffness. Further studies involving larger samples and longer follow-up periods are required to support the consolidation of this technique as an alternative or adjunct to pharmacological treatment.
Acute effect of whole-body photobiomodulation on arterial stiffness in individuals with hypertension: a double-blind, sham-controlled, randomized clinical trial
Keywords: Hipertensão; Rigidez arterial; Fotobiomodulação; LEDT; LLLT; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar